Hand Extremities and Effective Doses from Radiation Workers at the Nuclear Medicine Department, A. W. Sjahranie Hospital, Samarinda - Wahyu Andriyani; R. Zurma; E. R. Putri (LPPM Politeknik Aceh Selatan, 2026)
The use of radiopharmaceuticals in nuclear medicine increases the risk of radiation exposure for workers, particularly in the extremities and sensitive organs such as the lens of the eye and lungs. This study aims to determine the radiation dose received by three radio-pharmacists at the Nuclear Medicine Installation of RSUD A. W. Sjahranie Samarinda during the 2018–2023 period, and to compare the effective dose and hand extremity dose with the Dose Limit Values (NBD) set by ICRP and BAPETEN. The data were analysed using quantitative descriptive methods, based on readings from thermoluminescent dosimeters (TLD badge and ring dosimeter). The analysis included calculations of effective dose, extremity dose, mean values, and standard deviation. The results showed that Radio-pharmacist 2 had the highest effective dose to the eye lens (0.073 ± 0.02) mSv and lungs (0.18 ± 0.04) mSv, while Radio-pharmacist 3 had the highest hand extremity dose (33 ± 30,03) mSv. All doses recorded were below the Dose Limit Values (NBD) recommended by the ICRP, i.e., 20 mSv/year for internal organs and 500 mSv/year for extremities. The variation in dose among workers was influenced by the duration and technique of work, body positioning, and the effectiveness of protective equipment. This study highlights the importance of optimizing radiation protection and regularly monitoring individual doses to ensure the safety of nuclear medicine personnel.